Removal of Dinotefuran, Thiacloprid, and Imidaclothiz Neonicotinoids in Water Using a Novel Pseudomonas monteilii FC02–Duckweed (Lemna aequinoctialis) Partnership - Cai, Xiao-Yu; Xu, Man; Zhu, Yu-Xuan; Shi, Ying; Wang, Hong-Wei (Frontiers in Microbiology, 2022)
Neonicotinoids (NEOs) are the most widely used insecticides in the world and pose a serious threat to aquatic ecosystems. The combined use of free-floating aquatic plants and associated microorganisms has tremendous potential for remediating water contaminated by pesticides. The aim of this study was to determine whether plant growth-promoting bacteria (PGPB) could enhance the phytoremediation efficiency of duckweed (Lemna aequinoctialis) in NEO-contaminated water. A total of 18 different bacteria were isolated from pesticide-stressed agricultural soil. One of the isolates, Pseudomonas monteilii FC02, exhibited an excellent ability to promote duckweed growth and was selected for the NEO removal experiment. The influence of strain FC02 inoculation on the accumulation of three typical NEOs (dinotefuran, thiacloprid and imidaclothiz) in plant tissues, the removal efficiency in water, and plant growth parameters were evaluated during the 14-day experimental period. The results showed that strain FC02 inoculation significantly (p < 0.05) increased plant biomass production and NEO accumulation in plant tissues. The maximum NEO removal efficiencies were observed in the inoculated duckweed treatment after 14 days, with 92.23%, 87.75% and 96.42% for dinotefuran, thiacloprid and imidaclothiz, respectively. This study offers a novel view on the bioremediation of NEOs in aquatic environments by a PGPB-duckweed partnership.